Soil Microbial Activity and Diversity in Response to Soil Chemical Factors in Agricultural Soils - Lily Ishak; Philip Hugh Brown (JOURNAL OF TROPICAL SOILS, 2019)
The role of microbial communities in maintaining soil health is mostly influenced by chemical condition of soil. Microbial communities vary in response to soil chemical factors. The contradictive results from previous findings emphasise that it is difficult to define a pattern of the influence of soil chemical factors on soil microbial diversity and activity. The aim of the study was to assess soil microbial responses to soil chemical factors in agricultural soils. Composite soil (Dermosol order) samples taken from 16 commercial crop sites in Bundaberg, Queensland, Australia, were chemically and biologically analysed. It was found that bacterial and fungal activity and diversity were significantly affected by soil EC, SOM and NO3-N content, but were not influenced by soil pH, CEC, and Ca:Mg ratio. The diversity of bacterial and fungal communities displayed a positive linear relationship with soil EC, whereas the activity and diversity of these two microbial groups and SOM displayed a significant quadratic relationship. The finding suggested that microbial community was predominantly influenced by SOM content.